Acceptance and Use of Regional Government Information Systems Using the UTAUT2 Model - Ni Luh Putu Ika Satia Devi; Dodik Ariyanto (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2024)
Acceptance and use of information systems by local governments is a crucial aspect in increasing the efficiency, transparency and accountability of public services. However, the implementation of this technology often faces various challenges, both from a technical and non-technical side. The UTAUT2 model has proven to be a powerful framework for understanding user behavior in adopting information technology. This research aims to determine the factors that influence the acceptance and use of Regional Government Information Systems using the UTAUT2 model. The samples in this research were accounting and budgeting operators in each OPD with a sample size of 147. The data collection technique in this research was by distributing questionnaires via Google Form. The data analysis used is SEM-PLS analysis. The results of this study indicate that performance expectations have no effect on behavioral intentions. Effort expectations, facilitating conditions, confidence in using SIPD, habits have a positive influence on behavioral intentions. Behavioral intentions, performance expectations, effort expectations, facilitating conditions, confidence in using SIPD have a positive influence on usage behavior. Habits have no effect on usage behavior. The implications of this research are From a practical perspective, the results of this research can help local governments in designing more effective strategies to increase the adoption of information technology among employees and the community.